Empowerment through Batik Design and Manufacturing Training At Aisyiah Putri Bondowoso Orphanage - Trias setyowati; Fefi Nurdiana Widjayanti (OJS Universitas Muhammadiyah Gresik, 2020)
Foster children and caregivers in the orphanage Princess Aisha old Bondowoso many productive, but they have limited knowledge will be skills, as well as the shortage of funds for venture capital as well as to participate in skills training. These limitations make foster children and caregivers lack skills and do not have work experience. Proposer cooperation with SMEs Batik is Yuniar Batik to share knowledge and experience in mendesai n and make Batik, so as to help the orphanage Princess Aisha Bondowoso in terms of improving the skill set of foster children and their caregivers. By providing knowledge and experience on how to design and make batik, it is hoped that later foster children and caregivers of Putri Aisyah Bondowoso Orphanage will gain knowledge and skills in batik making. The Stimulus Community Partnership Program is implemented by establishing communication and collaboration between the executors of the University of Muhammadiyah Jember represented by Ms. Trias Setyowati, SE., SH., MM , and the 1st partner as a speaker is from Yuniar Batik, represented by the owner, namely the owner, namely the owner Yuniar Widiana, SP partner 2 is Orphanage daughter Aisha Bondowoso represented by Ms. Herni Mauludiyah, S.Pd.I ., In this case, act as coach and chaperone and pemonev activities. While partner 1 acts as a speaker and partner 2 acts as a participant in training and mentoring activities . To both work together to undertake community service activities with the title Empowerment through Training Design and Manufacture Batik at Panti Asuhan Putri Aisyah Bondowoso .